Discrepancy between Radiographic and Arthroscopic Findings of Thumb Basilar Joint Arthritis: A Preliminary Clinical Report. Issue 3 (13th March 2023) - Sun, Michael; Yoshida, Ryu; Tsai, Eugene; Kulber, David
Abstract : Background: The radiographic staging of arthritic changes in the thumb carpometacarpal (CMC) joint is known to have poor correlation with pain level. This may be due to the limited ability of radiographs to evaluate degenerative changes. The purpose of this study was to examine the relationship between radiographic versus arthroscopic findings of thumb CMC and scaphotrapeziotrapezoidal (STT) joint arthritis. Methods: Twenty patients with symptomatic thumb CMC arthritis underwent arthroscopy of thumb CMC and STT joints with concomitant synovectomy or arthroplasty depending on the degree of articular degeneration found. All patients had preoperative radiographs of the thumb CMC and STT joints. Radiographic degeneration was graded based on the Eaton-Glickel classification. Intraoperative arthroscopic images were reviewed and graded based on the Brown grading system. Results: At the thumb CMC joint, five patients had discordant radiographic and arthroscopic findings of arthritis. At the STT joint, one patient had discordant radiographic and arthroscopic findings of arthritis. Conclusions: In comparing the two staging systems, we found a small subset of patients that demonstrated significant discrepancies. Clinical evaluation remains essential, and patients should be informed that radiographs may underestimate the actual severity of arthritis.